2009
DOI: 10.4319/lo.2009.54.1.0062
|View full text |Cite
|
Sign up to set email alerts
|

Autochthonous and allochthonous contributions to mesozooplankton diet in a tidal river and estuary: Integrating carbon isotope and fatty acid constraints

Abstract: We examined the carbon sources used by bacteria and mesozooplankton in the Scheldt River and estuary (Belgium, The Netherlands) using a combined stable isotope and fatty acid composition approach. Water samples were collected monthly at six stations during 1 yr and analyzed for 13 C of dissolved inorganic carbon, dissolved organic carbon (DOC), and particulate organic carbon (POC). Mesozooplankton was determined up to family, genus, or species level and analyzed for 13 C and fatty acid content. Suspended parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
60
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 52 publications
9
60
0
Order By: Relevance
“…The enrichment in 13 C of carbohydrates and depletion in 13 C of lipids relative to total cells (mainly amino acids) has been shown in culture studies of phytoplankton (Van Dongen et al, 2002) and of several primary producers and consumers (Teece and Fogel, 2007). Results of this study show that the enrichment in 13 C in glucose as well as the 13 C-depletion in in fatty acids relative to bulk material can also be detected in field samples (Fig.…”
Section: Carbohydrates and Lipid δ 13 Csupporting
confidence: 53%
See 2 more Smart Citations
“…The enrichment in 13 C of carbohydrates and depletion in 13 C of lipids relative to total cells (mainly amino acids) has been shown in culture studies of phytoplankton (Van Dongen et al, 2002) and of several primary producers and consumers (Teece and Fogel, 2007). Results of this study show that the enrichment in 13 C in glucose as well as the 13 C-depletion in in fatty acids relative to bulk material can also be detected in field samples (Fig.…”
Section: Carbohydrates and Lipid δ 13 Csupporting
confidence: 53%
“…In laboratory studies, the offset between lipids and bulk material has been shown to be variable (van Dongen et al, 2002, Fiorini et al, 2010. One can expect that in field studies, with multiple species, however, these cellular variations would probably disappear within broader trends.…”
Section: Phytoplankton δ 13 Cmentioning
confidence: 99%
See 1 more Smart Citation
“…However, POM is composed by both phytoplankton and detritus or different origins (both aquatic and terrestrial), and it can be difficult to separate the contributions of the two, although the latter can be constrained using for example chlorophyll a:POC ratios or POC:PN ratios (e.g., Kendall et al 2001). On the other hand, zooplankton feeds both on the detritus and algae fractions of POM, but in a selective manner, depending on the relative abundance of these sources (Cole et al 2006, Van den Meersche et al 2009). A similar situation occurs in the benthic food chains, where benthic algae and organic matter of different origins are differentially assimilated by phytodetritivorous species (D'Avanzo and Valiela 1990).…”
Section: Introductionmentioning
confidence: 85%
“…In addition, the isotopic signature of a consumer could result from consumption of a single food source, but more realistically usually reflects consumption of a mixture of §2 food sources. One way to gain a better understanding of the relative importance of basal food sources in food webs is to combine analysis of stable-isotopic composition with analysis of phospholipid-derived fatty acid (PLFA) composition (Kharlamenko et al 2001, Perga et al 2006, Van den Meersche et al 2009). The PLFA approach is based on the specific PLFA composition of bacteria and algae and on the inability of animals to synthesize specific PLFAs and essential polyunsaturated fatty acids (PUFAs; Kharlamenko et al 2001).…”
mentioning
confidence: 99%